A preparation method and application of halide solid electrolyte

The halide solid electrolyte of lithium-ion batteries is prepared through cross-layer laying structure combined annealing process, which solves the problems of cumbersome preparation process and poor electrochemical performance in the prior art, and achieves efficient and stable electrochemical performance, which is suitable for the application of all-solid lithium batteries.

CN116443914BActive Publication Date: 2025-03-18YANGTZE UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310299996.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-26
Publication Date
2025-03-18
Estimated Expiration
2043-03-26

AI Technical Summary

Technical Problem

In the prior art, the preparation process of solid-state electrolytes is complicated and the electrochemical performance is poor, which limits its application in the field of all-solid-state batteries.

Method used

The halide solid electrolyte of lithium-ion batteries is prepared by cross-layer laying structure combined annealing process. The lithium source and metal halide are uniformly mixed by ball milling, and cross-layered with ammonium salt in multiple layers on the crucible, and annealed in an inert protective atmosphere.

Benefits of technology

It realizes a halide solid electrolyte with simple operation, uniform product composition and stable properties, with good air stability and excellent electrochemical properties, and is suitable for the application of all-solid lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116443914B_ABST
    Figure CN116443914B_ABST
Patent Text Reader

Abstract

The present invention discloses a preparation method and application of a halide solid electrolyte for lithium-ion batteries, and belongs to the field of new energy technology. The preparation method of the solid electrolyte comprises the following steps: S1, ball-milling and mixing a lithium source and a metal halide in a certain stoichiometric ratio to obtain a mixed powder; S2, cross-spreading the mixed powder obtained in step S1 and a certain stoichiometric amount of ammonium salt in multiple layers in a crucible, annealing in a protective atmosphere, and obtaining a target halide solid electrolyte after cooling with the furnace. The present invention also proposes a lithium-ion battery, which consists of a positive electrode sheet, a halide solid electrolyte, a sulfide interlayer and metallic lithium. The method is simple, and the conductivity of the obtained halide solid electrolyte is 0.34mS / cm. The LiNi assembled from the electrolyte 0.83 Co 0.11 Mn 0.06 O 2 |Li 3 YC 6 |Li 6 PS 5 The Cl|Li battery exhibits a first-cycle discharge specific capacity of up to 191.5 mAh / g and a capacity retention rate of 89.5%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy batteries, and in particular to a preparation method of a halide solid electrolyte and application thereof. Background Art

[0002] Lithium-ion batteries play an extremely important role in people's daily life and industrial production due to their advantages such as high energy density, long cycle life, and high charge and discharge efficiency. Traditional liquid lithium-ion batteries use flammable organic liquid electrolytes, which have safety hazards of flammability and explosion. The presence of solid electrolytes can significantly improve the safety of batteries. Their high mechanical strength can inhibit the excessive growth of lithium dendrites at the interface between electrolyte and lithium metal anode to a certain extent, making the application of metal lithium anode possible, thereby greatly improving the energy density of batteries. Therefore, solid electrolytes are considered to be the next generation of key energy storage devices with great prospects. Ideal solid electrolyte materials should have the advantages of high ionic conductivity, low electronic conductivity, wide electrochemical stability window and compatibility with electrode materials. At present, there are two types of solid electrolytes that have been widely studied and whose room temperature ionic conductivity is close to or even exceeds the level of liquid electrolytes: oxide solid electrolytes and sulfide solid electrolytes, but these two types of solid electrolytes still have some disadvantages. Sulfide electrolytes are chemically unstable in the air, resulting in reduced ionic conductivity and the production of toxic H2S gas; oxide electrolytes require high-temperature sintering, which increases the cost of battery manufacturing and is prone to interfacial reactions. The above problems limit the application of the two in the field of all-solid-state batteries. The existing electrolyte preparation process is cumbersome and has poor electrochemical performance. Therefore, developing a simple, feasible and universal process to prepare solid electrolytes with excellent electrochemical performance is crucial to the development of all-solid-state batteries. Summary of the invention

[0003] The purpose of the present invention is to overcome the above technical deficiencies, provide a method for preparing a halide solid electrolyte for a lithium ion battery and its application, and solve the technical problems in the prior art that the preparation process is complicated and the electrochemical performance of the prepared halide solid electrolyte is poor.

[0004] In order to achieve the above technical objectives, the technical solution of the present invention provides a method for preparing a lithium-ion battery halide solid electrolyte and its application.

[0005] The present invention provides a method for preparing a halide solid electrolyte, comprising the following steps:

[0006] S1, mixing the lithium source and the metal halide by ball milling according to a certain stoichiometric ratio to obtain a mixed powder;

[0007] S2, the mixed powder obtained in step S1 and the ammonium salt powder in a certain stoichiometric ratio are evenly spread in multiple layers in a crucible, annealed in an inert protective atmosphere, and cooled in the furnace to obtain the target halide solid electrolyte.

[0008] Further, in step S1, the lithium source is one or more of lithium chloride, lithium bromide, lithium fluoride, lithium carbonate, lithium acetate, lithium hydroxide, lithium nitrate, lithium lactate, lithium oxalate, lithium oxide, lithium formate, lithium hydrogen phosphate, lithium dihydrogen phosphate, lithium ammonium phosphate and lithium diammonium phosphate.

[0009] Furthermore, in step S1, the metal element in the metal halide is one or more of Sc, Y, La-Lu lanthanide elements, Al, Ga, and In.

[0010] Furthermore, in step S1, the molar ratio of the lithium source to the metal halide is 3:1.

[0011] Further, in step S2, the ammonium salt is one or more of ammonium chloride, ammonium fluoride, ammonium iodide, ammonium bromide, ammonium nitrate, ammonium carbonate, ammonium sulfate, ammonium bifluoride, and ammonium bicarbonate.

[0012] Furthermore, in step S2, the stoichiometric ratio of the ammonium salt to the metal halide in the mixed powder is (3-20):1, preferably (9-12):1.

[0013] Furthermore, in step S2, the inert protective atmosphere is argon or nitrogen.

[0014] Furthermore, in step S2, the annealing is carried out in two stages, the temperature of the first stage is 50-300°C, the insulation time is 2-10h, and the temperature of the second stage is 300-900°C, the insulation time is 2-20h.

[0015] Furthermore, in step S2, the first stage of annealing is at a temperature of 100-250°C for a holding time of 2 hours, and the second stage is at a temperature of 300-550°C for a holding time of 4-7 hours.

[0016] Furthermore, the specific method of the multi-layer cross-uniform paving in step S2 is: the ammonium salt powder and the mixed powder in step S1 are cross-paved in the crucible in multiple layers in a structure of ammonium salt powder, mixed powder, ammonium salt powder, mixed powder... from bottom to top, wherein the thickness of each ammonium salt layer must be greater than that of the mixed powder layer.

[0017] In addition, the present invention also includes the use of the above-mentioned halide solid electrolyte in a lithium ion battery.

[0018] The present invention also provides a lithium-ion battery, which is composed of a positive electrode plate, the above-mentioned halide solid electrolyte, a sulfide interlayer and metallic lithium.

[0019] Compared with the prior art, the beneficial effects of the present invention include: the cross-layer structure combined with annealing process used in the present invention is a general method for preparing halide solid electrolytes, which has the advantages of simple operation, uniform product composition and stable properties. The halide solid electrolyte obtained by this method has good air stability, excellent electrochemical performance and good compatibility with oxide positive electrode materials. The method is simple, and the conductivity of the halide solid electrolyte obtained is 0.34mS / cm. The LiNi assembled from the electrolyte 0.83 Co 0.11 Mn 0.06 The O2|Li3YCl6|Li6PS5Cl|Li battery exhibits a first-cycle discharge specific capacity of up to 191.5mAh / g. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is an XRD pattern of the Li3YCl6 solid electrolyte obtained when the first stage temperature is 200°C and the second stage temperature is 400°C, 450°C, 500°C, and 550°C in Example 1 of the present invention;

[0021] Figure 2 This is a SEM image of the Li3YCl6 solid electrolyte obtained when the first stage temperature is 200°C and the second stage temperature is 500°C in Example 1 of the present invention;

[0022] Figure 3 LiNi is composed of Li3YCl6 solid electrolyte prepared at different second-stage temperatures in Example 1 of the present invention. 0.83 Co 0.11 Mn 0.06 First charge and discharge curves of O2|Li3YCl6|Li6PS5Cl|Li battery.

[0023] Figure 4 The LiNi is composed of the Li3YCl6 solid electrolyte prepared in Example 1 of the present invention at a first stage temperature of 200°C and a second stage temperature of 500°C. 0.83 Co 0.11 Mn 0.06 Specific capacity-efficiency cycle curve of O2|Li3YCl6|Li6PS5Cl|Li battery. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0025] Example 1

[0026] This embodiment provides a halide solid electrolyte, which is prepared by the following steps:

[0027] S1. Weigh lithium chloride and yttrium chloride according to a stoichiometric ratio (i.e., molar ratio) of 3:1, place the mixture in a ball mill, and grind the mixture to obtain a uniform mixed powder;

[0028] S2. Weigh ammonium chloride according to a molar ratio of ammonium chloride to yttrium chloride of 9:1 to obtain ammonium salt powder, and cross-lay it in a crucible with the mixed powder described in step S1 in multiple layers in a structure of ammonium salt powder, mixed powder, ammonium salt powder, mixed powder, etc. from bottom to top, ensuring that the thickness of each ammonium salt layer is greater than the thickness of the mixed powder layer.

[0029] S3. Place the crucible described in S2 in a nitrogen atmosphere tubular furnace for annealing. The annealing is carried out in two stages. First, the temperature is increased from room temperature to 200°C at a heating rate of 2°C / min and kept for 2 hours for one stage of annealing. Then, the temperature is increased to 400°C, 450°C, 500°C and 550°C respectively and kept for 5 hours for a second stage of annealing. After cooling in the furnace, the target product Li3YCl6 solid electrolyte is obtained, which is placed under a pressure of 3.5T for cold pressing to prepare Li3YCl6 solid electrolyte ceramic sheets.

[0030] Figure 1 It can be seen that the Li3YCl6 solid electrolyte can be successfully prepared when the second stage temperature is higher than 400℃; Figure 2 It can be seen that the solid electrolyte prepared at the second temperature of 500°C is nanoparticles.

[0031] LiNi 0.83 Co 0.11 Mn 0.06 The O2 positive electrode, Li3YCl6 solid electrolyte ceramic, Li6PS5Cl sulfide interlayer and metallic lithium were assembled into an all-solid-state lithium battery, and its battery performance was investigated in the voltage range of 2.8-4.3 V. The battery was charged and discharged at a current density of 0.1C, and its electrochemical performance at room temperature is shown in Table 1.

[0032] Table 1 Experimental conditions and results of Example 1

[0033]

[0034]

[0035] Note: The capacity retention rates in the specific embodiments of the present invention are all the capacity retention rates after 100 cycles.

[0036] From Table 1 and Figure 1It can be seen that the electrochemical performance of the halide solid electrolyte at the second stage temperature of 400 °C is lower than that of the halide solid electrolyte at other temperatures, indicating that the second stage temperature affects the crystallinity of the solid electrolyte, and then affects its electrochemical performance; From Table 1 and Figure 3 , 4 It can be seen that when the temperature of the second stage of Example 1 is 500°C, the prepared halide solid electrolyte exhibits the best electrochemical performance, with an ion conductivity of up to 0.34 mS / cm, a first discharge specific capacity of up to 191.5 mAh / g, a first coulombic efficiency of up to 86.69%, and a capacity retention rate of up to 89.5%.

[0037] Example 2

[0038] This embodiment provides a halide solid electrolyte, which is prepared by the following steps:

[0039] S1. Weigh lithium chloride and yttrium chloride according to the stoichiometric ratio of 3:1, place them in a ball mill and grind them to obtain a uniform mixed powder;

[0040] S2, weighing ammonium chloride according to the molar ratio of ammonium chloride to yttrium chloride of 3:1, 6:1, 9:1 and 12:1 to obtain ammonium salt powder, and respectively laying it in a crucible with the mixed powder in step S1 in multiple layers in a structure of ammonium salt powder, mixed powder, ammonium salt powder, mixed powder, etc. from bottom to top, ensuring that the thickness of each ammonium salt layer is greater than the thickness of the mixed powder layer;

[0041] S3. Place the crucible described in S2 in a nitrogen atmosphere tubular furnace for annealing. The annealing is carried out in two stages. First, the temperature is increased from room temperature to 200°C at a heating rate of 2°C / min and kept for 2 hours for a first stage of annealing. Then the temperature is increased to 500°C and kept for 5 hours for a second stage of annealing. After cooling in the furnace, the target product Li3YCl6 solid electrolyte is obtained. It is placed under a pressure of 3.5T for cold pressing to prepare Li3YCl6 solid electrolyte ceramic sheets.

[0042] LiNi 0.83 Co 0.11 Mn 0.06 The O2 positive electrode sheet, Li3YCl6 solid electrolyte ceramic sheet, Li6PS5Cl sulfide interlayer and metallic lithium were assembled into an all-solid-state lithium battery, and its battery performance was investigated in the voltage range of 2.8-4.3 V. The charge and discharge were carried out at a current density of 0.1C, and its electrochemical performance is shown in Table 2.

[0043] Table 2 Experimental conditions and results of Example 2

[0044]

[0045] It can be seen from Table 2 that at the same second-stage annealing temperature, different stoichiometric ratios of ammonium salt to metal halide will affect its electrochemical performance.

[0046] Example 3

[0047] This embodiment provides a solid electrolyte, which is prepared by the following steps:

[0048] S1. Weigh lithium chloride and yttrium chloride according to the stoichiometric ratio of 3:1, place them in a ball mill and grind them to obtain a uniform mixed powder;

[0049] S2, ammonium chloride is weighed according to a molar ratio of ammonium chloride to yttrium chloride of 9:1 to obtain ammonium salt powder, and the ammonium chloride powder and the mixed powder in step S1 are cross-laid in a crucible in multiple layers in a structure of ammonium salt powder, mixed powder, ammonium salt powder, mixed powder, etc. from bottom to top, and the thickness of each ammonium salt layer is ensured to be greater than the thickness of the mixed powder layer during the process;

[0050] S3. Place the crucible described in S2 in a nitrogen atmosphere tubular furnace for annealing. The annealing is carried out in two stages. First, the temperature is increased to 200°C at a heating rate of 2°C / min and kept at this temperature for 2h for one stage of annealing. Then, the temperature is kept at 500°C for 4h, 5h, 6h and 7h respectively for two stages of annealing. After cooling in the furnace, the target product Li3YCl6 solid electrolyte is obtained. It is placed under a pressure of 3.5T for cold pressing to prepare Li3YCl6 solid electrolyte ceramic sheets.

[0051] LiNi 0.83 Co 0.11 Mn 0.06 The O2 positive electrode, Li3YCl6 solid electrolyte ceramic, Li6PS5Cl sulfide interlayer and metallic lithium were assembled into an all-solid-state lithium battery, and its battery performance was investigated in the voltage range of 2.8-4.3 V. The battery was charged and discharged at a current density of 0.1C, and its electrochemical performance is shown in Table 3.

[0052] Table 3 Experimental conditions and results of Example 3

[0053]

[0054] It can be seen from Table 3 that at the same second-stage temperature, different holding times have little effect on the ionic conductivity and first discharge specific capacity of the solid electrolyte.

[0055] Example 4

[0056] The solid electrolyte was prepared according to the method of Example 1, except that the first annealing temperature was controlled to 100°C, 150°C, 200°C, and 250°C, and the second annealing temperature was 500°C, and the rest was the same as Example 1. The electrochemical properties are shown in Table 4.

[0057] Table 4 Experimental conditions and results of Example 4

[0058]

[0059]

[0060] It can be seen from Table 4 that at the same second-stage temperature, different first-stage temperatures have little effect on the electrochemical properties of the solid electrolyte.

[0061] Example 5

[0062] The solid electrolyte was prepared according to the method of Example 1, except that the metal halide was indium chloride, the second annealing temperature was controlled to 300°C, 330°C, 360°C, and 390°C, respectively, and the rest was the same as Example 1. The electrochemical properties are shown in Table 5.

[0063] Table 5 Experimental conditions and results of Example 5

[0064]

[0065] It can be seen from Table 5 that the Li3InCl6 solid electrolyte obtained at the second stage temperature of 330℃ exhibits the best electrochemical performance.

[0066] The present invention adopts a cross-layer structure combined with an annealing process to prepare a Li-MX halide solid electrolyte (M represents a metal, and X represents a halogen), wherein a lithium salt and a metal halide are uniformly mixed by ball milling, and then cross-layered with an ammonium salt in a crucible in multiple layers, and then annealed in a tubular protective atmosphere furnace to obtain halide solid electrolyte particles having excellent air stability and electrochemical properties.

[0067] In the above embodiments, the added lithium source can also be selected from one or more of lithium fluoride, lithium carbonate, lithium acetate, lithium hydroxide, lithium nitrate, lithium lactate, lithium oxalate, lithium oxide, lithium formate, lithium hydrogen phosphate, lithium dihydrogen phosphate, lithium ammonium phosphate or lithium diammonium phosphate.

[0068] In the above embodiments, the metal element in the added metal halide can also be one or more metal halides of Sc, Y, La-Lu lanthanide elements, Al, Ga, In, such as indium chloride, erbium chloride, yttrium bromide, lanthanum bromide, etc.

[0069] In the above embodiments, the added ammonium salt may also be one or more of ammonium chloride, ammonium fluoride, ammonium iodide, ammonium bromide, ammonium nitrate, ammonium carbonate, ammonium sulfate, ammonium bifluoride, and ammonium bicarbonate.

[0070] The key points of the present invention are that, taking ammonium chloride as an example, first, an intermediate compound of nNH4Cl˙MCl3 can be formed. After reaching the decomposition temperature of the ammonium salt, the ammonia gas and hydrogen chloride gas generated by the decomposition of the excess ammonium salt can protect the generated halide from being hydrolyzed; second, a cross-layer post-laying structure is used for annealing, and the gaseous HCl passes through the mixed powder layer of the lithium source and the metal halide when volatilizing from the lower layer to the upper layer, and has sufficient gas-solid surface contact with the mixed powder, chlorinating the possible M2O3 and MOCl side reaction products, so as to make the reaction more complete and the product purer, so as to achieve the purpose of obtaining a target halide solid electrolyte with high purity and excellent electrochemical performance. This method is applicable to the preparation of a variety of halide solid electrolytes.

[0071] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A method for preparing a halide solid electrolyte, characterized in that: The following steps are involved: S1. Mix lithium chloride and yttrium chloride by ball milling at a stoichiometric ratio of 3:1 to obtain a mixed powder; S2, the mixed powder obtained in step S1 and the ammonium chloride powder are evenly spread in a crucible in multiple layers in a stoichiometric ratio of 9:1, and then annealed in an inert protective atmosphere, and the target halide solid electrolyte is obtained after cooling in the furnace; The specific method of the multi-layer cross-even paving in step S2 is: the ammonium chloride powder and the mixed powder in step S1 are cross-paved in the crucible in multiple layers in a structure of ammonium chloride powder, mixed powder, ammonium chloride powder, mixed powder, etc. from bottom to top, wherein the thickness of each ammonium chloride layer must be greater than that of the mixed powder layer; In step S2, the annealing is carried out in two stages, the temperature of the first stage is 50-300°C, the insulation time is 2-10h, and the temperature of the second stage is 500°C, the insulation time is 4-7h.

2. A lithium-ion battery, which consists of a positive electrode sheet, a halide solid electrolyte prepared by the preparation method according to claim 1, a sulfide interlayer and metallic lithium.

Citation Information

Patent Citations

  • Preparation method of anhydrous cerium chloride

    CN108455650A

  • Preparation method of lithium yttrium halide and application thereof in solid electrolyte and battery

    CN109775744A

  • Halide solid electrolyte and preparation method and application thereof

    CN113363567A

  • Halide solid electrolyte powder material, preparation method thereof and solid-state battery

    CN115332616A